A practical development protocol for evidence-based digital integrative arts therapy content in public mental health services: digital transformation of mandala art therapy - Kim, Hyungsook; Choi, Yoonyoung (Frontiers in Public Health, 2023)
Introduction The fundamentals of digital transformation include the conversion of the traditional method into a digital format to develop a standardized system that collects, analyzes, and processes quantitative data. This study aims to provide a comprehensive understanding of the development process and key elements of evidence-based digital integrative arts therapy. Methods The “Digital Mandala” service in the “Mental Health App” produced as part of a national public mental health project for personalized depression management is adopted to explain how to convert the existing mandala art therapy into digital format. A living lab approach has been applied, which can be used to address the nation's mental health challenges by promoting collaboration, innovation, and evidence-based solutions. Results Evidence-based digital content requires evidence that covers the structural process, the effects of existing methods, and the components and meanings of each detailed scene. In this section, we provide five stages of the development process, including preliminary research, design, development, commercialization, and advancement. Consequently, clinical elements, integrative arts therapy features, and data factors are defined as the key principles of evidence-based digital integrative arts therapy. Discussion Based on the data factors found in this study, it will be possible to create an evaluation dataset of digital integrative arts therapy content for managing depression. Additionally, the large-scale public data can be analyzed through artificial intelligence technology, which is expected to be used as a basis for deriving significant results in a new form, going further than the existing evaluation method. This research is significant because it establishes the foundation for digital transformation in the field of art therapy for public mental health services and investigates its potential.